Hans Christian Andersen and the city of Paris - Jørgensen, Kristina Junge (Aktualitet - Litteratur, kultur og medier, 2019)
Hans Christian Andersen visited Paris 8 times, and if we compute these journeys, he spent in all about 10 months in the French capital. In this paper, I examine the importance these journeys have had on Andersen’s literary production. I describe four different themes in which Andersen portrays the French capital: Paris on the Grand Tour, Paris as the city of theatre, Napoleon’s Paris, and the Metropolitan Paris. There’s no doubt that for Andersen, Paris was the city that had it all. In several of Andersen’s works and letters, he refers to Paris as the “city of the cities.” This expression is constantly used today when the Danes talk about Paris. In my article, I argue that the Danes might have inherited this expression from Andersen as he was the first one to name Paris “the city of cities” in a publication in Denmark.